"Why I quit journalism:" Former journalists' advice giving as a way to regain control. (January 2023) - Mathews, Nick; Bélair-Gagnon, Valérie; Carlson, Matt
This study offers a metajournalistic discourse analysis of first-person narratives by former journalists who quit the profession. It finds the former journalists felt powerless while in the industry. They expressed this by writing about feelings of being stuck in their "dream job, " haunted by an always-on mentality, strained mentally overall, and unsupported by the industry and colleagues. This article argues that with these texts, the former journalists regained a sense of power over the industry by offering advice to other journalists about leaving the industry. As with any profession, advice giving in journalism has always occurred in myriad interpersonal settings with a variety of actors, from educators to colleagues to friends. Mediated advice would occur within the relatively restricted realm of journalism trade press. Yet self-publishing digital platforms provide public outlets for advice giving, including to former journalists who have lost their news platform for speaking to the public.